2008
DOI: 10.1063/1.3003079
|View full text |Cite
|
Sign up to set email alerts
|

Color control of white photoluminescence from carbon-incorporated silicon oxide

Abstract: Color control of the white photoluminescence (PL) from carbon-incorporated silicon oxide is demonstrated. The carbon-incorporated silicon oxide was fabricated by carbonization of porous silicon in acetylene flow (at 650 and 850 °C) followed by wet oxidation (at 650 and 800 °C). It was shown that PL color can be controlled in the range of blue-white and yellow-white by selecting the porosity of starting porous silicon as well as the carbonization and oxidation temperatures. Low-temperature oxidation resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 15 publications
2
35
0
Order By: Relevance
“…This behavior could be attributed to the existence of SiC x or SiC x O y nanoclusters, which have been proposed as the luminescence source in C-doped silicon oxides. 11 If the average size of SiC x clusters becomes smaller when annealed in O 2 , and as expected from quantum confinement effect, photon energies of associated optical transitions would blueshift. But oxidation of SiC x is unlikely to occur as low as 500°C, due to the strength of Siu C bonds.…”
mentioning
confidence: 99%
“…This behavior could be attributed to the existence of SiC x or SiC x O y nanoclusters, which have been proposed as the luminescence source in C-doped silicon oxides. 11 If the average size of SiC x clusters becomes smaller when annealed in O 2 , and as expected from quantum confinement effect, photon energies of associated optical transitions would blueshift. But oxidation of SiC x is unlikely to occur as low as 500°C, due to the strength of Siu C bonds.…”
mentioning
confidence: 99%
“…By analogy with Refs. [20] and [21] and our PL results described in the previous part, the origin of the broad EL band in our structure can be attributed to radiative transitions of the electronic states associated with C SiO  bonds or carbon nanoclusters. Additionally, some contribution of the light emission associated with the excitation of non-bridging oxygen hole centers can be expected around 620 nm [24].…”
Section: Electroluminescencementioning
confidence: 66%
“…The nature of the wide broad PL band is unclear up to date. But it can be suggested that in green-red region the PL can be associated with amorphous carbon nanoclusters [19,20] and/or carbon-related defects [21]. Some part of the PL band in blue region could be attributed to luminescence from defects located in silicon dioxide matrix such as neutral oxygen vacancies [22].…”
Section: Photoluminescencementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been demonstrated that carbon incorporated silicon oxide nanostructured materials exhibit a strong white photoluminescence (PL). Intriguing is that white PL was demonstrated by SiOC materials fabricated by quite different methods, namely: SiOC thin films deposited by thermal chemical vapor deposition (TCVD) [1], atmospheric pressure microplasma jet deposition [2], magnetron sputtering deposition [3], C + implantation into SiO 2 [4][5][6], chemical vapor deposition technique [7], carbonization/oxidation of porous silicon [8,9], sol-gel method [10].…”
Section: Introductionmentioning
confidence: 99%